(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
We address the Companhia Circense de Teatro e Bonecos from the meeting of puppeteer artists Sandra Cordeiro, Silvana Cartágenes and Beto Bittencourt and the creation of the play O Desejo de Catirina: o auto de Bumba Meu Boi, in 1991. We use the memories of the same artists through conversations, enterviews; publications research, folders, newspaper reports and other publicizing documents to create this text. From the circus adaptation of “auto popular do Bumba Meu Boi” to the puppet theater with the use of multiple languages, we seek to identify its contributions to the dramaturgy of Maranhão.